Philippine inequality across the twentieth century slim evidence, but fat questions - Williamson, Jeffrey G. (2017)
In spite of persistent debates about income inequality and pro-poor policy in the Philippines, its history over the past century has been ignored, at least by economists. This is surprising given that the Philippines already had its first census in 1903, long before its neighbors, augmented by other relevant evidence embedded in official documents generated by the American insular government. It is also surprising given that we know that income distributions change only very slowly and must be examined over the long run to identify its drivers. This essay reviews the thin historical evidence and proposes explanations. There is no Kuznets Curve, and no Marxian, Pikettian, or other grand endogenous inequality theory at work, but there are dramatic episodes of change. It appears that there was an inequality rise up to World War 1, a fall between the world wars, a rise to high levels by the 1950s, and an almost certain rise up to the end of the century which, due to mismeasurement, looks instead like stasis. We need to collect better evidence to confirm these narratives and to assess competing hypotheses.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 56-60).
Keywords: Income distribution -- Philippines